1987
DOI: 10.1044/jshd.5204.393
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Application of Two Phonologically Based Treatment Procedures

Abstract: Two phonological process-based treatment procedures were applied in an ongoing clinical program. Subjects were 4 children aged 3:1, 3:8, 4:1, and 5:1. Two subjects were assigned to a minimal pairs contrasting procedure, and 2 were assigned to a modified cycles procedure based on results of a detailed phonological analysis. All children demonstrated marked changes in their phonological systems as shown by the results of pretreatment and follow-up generalization probes. Correct production generalized to sounds a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
61
1
16

Year Published

1991
1991
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(83 citation statements)
references
References 0 publications
5
61
1
16
Order By: Relevance
“…The results showed that the error patterns were suppressed in more than 90% of probes, and that there was local and within set generalization. Similar findings were made by Tyler, Edwards and Saxman (1987) who reported on two children receiving three 1-hour sessions per week. Three error patterns were suppressed using 5-10 minimal pairs per error pattern in a total of 8 and 9 hours of therapy.…”
Section: S89)supporting
confidence: 75%
See 1 more Smart Citation
“…The results showed that the error patterns were suppressed in more than 90% of probes, and that there was local and within set generalization. Similar findings were made by Tyler, Edwards and Saxman (1987) who reported on two children receiving three 1-hour sessions per week. Three error patterns were suppressed using 5-10 minimal pairs per error pattern in a total of 8 and 9 hours of therapy.…”
Section: S89)supporting
confidence: 75%
“…The mean increase in PCC was over 16%; on average children suppressed two major error patters (e.g., stopping, cluster reduction) and added four singleton speech sounds and six clusters to their phonetic repertoires. The rate and extent of progress is similar to that reported for minimal contrasts by Crosbie, Holm, and Dodd (2005), Tyler, Edwards, and Saxman (1987) and Weiner (1981). These clinical research studies provided between 6 and 14 hours of intervention.…”
Section: Progress In Interventionsupporting
confidence: 65%
“…As applied to the clinical domain, complexity at an epistemic level begins with the assessment process in the initial description of a child's errored sound system. For example, to adequately characterize a given child's pattern of errors, it may be necessary to appeal to multiple and varied phonological processes, and these may further interact (e.g., Dean, Howell, Waters, & Reid, 1995;Greenlee, 1974;Tyler, Edwards, & Saxman, 1987). This phonological description, in turn, may warrant an increased number of treatment goals to bring the child's sound system into conformity with the target language.…”
Section: Operational Definition Of Complexitymentioning
confidence: 99%
“…Dentre os modelos de terapia com base fonológica mais utilizados destacam-se: o de Ciclos Modificado 12 ; o ABAB-Retirada e Provas Múltiplas 13 ; e o de Oposições Máximas Modificado 14 . O Modelo de Ciclos Modificado é composto de ciclos de terapia, sendo que, em cada ciclo, três processos alvos são trabalhados, através de dois sons-alvo.…”
Section: Descritoresunclassified